Harmony Search Algorithm with Adaptive Parameters to Optimize the Linear Quadratic Regulator Design - Nascimento, L.B.P.; Pinto, V.P.; Amora, M.A.B. (Revista IEEE América Latina, 2018)
Linear Quadratic Regulator (LQR) is an important control technique with excellent properties associated to robust stability. This technique has been the subject of constant study until the present day, since the problems weighting matrices Q and R are still open, as well as the situations in which the dynamics is unknown. This work proposes the application of a novel Harmony Search (HS) algorithm to find the Q and R matrices. This algorithm ensures the automatic adjustment of parameters. By adopting the CH-47 helicopter and an inverted pendulum system, several tests involving search and simulations have been performed with two HS algorithms i.e. standard HS and Statistical Dispersion Harmony Search (SDHS). The latter one can be seen as the main contribution of this work, which also compares the results obtained from the algorithms